EXPERIENCE OF TREATMENT OF JUVENILE ANKYLOSING SPONDYLITIS WITH EYES LESION WITH ADALIMUMAB - E.I. Alexeeva; S.I. Valieva; T.M. Bzarova; A.O. Lisitsin; N.A. Karagulyan (Вопросы современной педиатрии)
This article presents a case report of juvenile ankylosing spondylitis and severe uveitis. A successful treatment with biological agent adalimumab was described. Administration of this medication induced the remission of uveitis, and it allowed surgical treatment of complicated cataract. Treatment of adalimumab resulted in increase of acuity of vision and improvement of quality of life.Key words: children, juvenile ankylozing spondylitis, rheumatoid uveitis, adalimumab.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(1):135-141)